Sediment exposure decreases diversity in the surface mucus layer microbiome of Porites lobata at Honoliʻi, Hawaiʻi - Nakoa, Joseph W. P.; Burns, John H. R.; Pascoe, Makoa; Cortes, Manuela; Ferreira, Sofia B.; Pascoe, Kailey H.; Kane, Haunani H.; Kapono, Clifford A. (Frontiers in Microbiology, 2025)
IntroductionCoral reefs are diverse marine ecosystems that provide essential ecological services, yet they are becoming increasingly degraded by anthropogenic stressors. Sediment deposition from land-based runoff can smother corals, reduce light availability, and alter the chemical and microbial composition of the water column. Prolonged sediment exposure disrupts coral-associated microbial communities, particularly within the surface mucus layer (SML), a physical barrier that mediates host–microbe interactions.MethodsWe investigated shifts in the SML microbiome of Porites lobata corals in response to an acute sedimentation event at Honoliʻi, Hawaiʻi. Microbial community structure was characterized using 16S rRNA gene sequencing, at three time points, before, during, and after the sedimentation event, to identify changes in microbial composition and diversity.ResultsSedimentation caused a significant decline in microbial diversity and shifted community composition, with the most pronounced changes observed post-sedimentation. Indicator species analyses identified 206 bacterial taxa associated with specific sedimentation periods, including enrichment of Flavobacteriaceae during sedimentation and dominance of Endozoicimonaceae after sedimentation.DiscussionThese findings demonstrate that sedimentation induces both immediate and delayed shifts in the SML microbiome, with potential implications for coral resilience. This study advances our understanding of how sedimentation affects coral-associated microbiomes and emphasizes the need to investigate the functional roles of microbial taxa involved in community transitions and recovery to inform conservation strategies.